The value of ecological and morphological features of the rain worms (Lumbricidae) of Steppe Dnieper and the influence of environmental factors in the organization of groups of natural, agricultural and urbanized ecosystems - Жуков, О. В.; Шаталін, Д. Б. (Scientific Progress & Innovations, 2016)
The paper offers a matrix of environmental and ecological-morphological features of earthworms. It is shown that this matrix has information that could explain the organization and functional structure of the community of earthworms of natural, agricultural and urbanized ecosystems. Humidity conditions, which are expressed by quantitative characteristics of gigrotop of the edaphotop are the determining factor that affects the organization of communities of earthworms, which, in its turn, is also reflected in the ecological and morphological features of lumbricid communities. Trophotopes has a multi-vector impact on the organization of communities of earthworms. Features of this influence are also modulated ceonotic features of the biocenoses. It showed that character of communications of humidity conditions and trophic edaphotop with the organization of communities of earthworms, which also is reflected in the morpho-ecological features of certain types of earthworms. Proofs of existence of earthworms ecomorphes – gigromorphes and trophocenomorphes have been presented.